2019
DOI: 10.1101/578211
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zika virus seroprevalence declines and neutralization antibodies wane in adults following outbreaks in French Polynesia and Fiji

Abstract: § These authors contributed equally InterpretationThe observed patterns of long-term anti-ZIKV antibody levels following outbreaks in the Pacific could be an early indication of the dynamics of population immunity in Latin America. Given that ZIKV antibody levels can wane substantially over time, follow-up seroprevalence studies and prospective clinical trial designs in LatinAmerica may need to be revised, and assumptions about the potential for ZIKV to reemerge may need to be revisited. FundingPacific Funds, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…The duration of protective immunity induced by ZIKV infection remains uncertain, since immunity to ZIKV infection was not studied extensively before the 2013 outbreaks. Evidence from seroprevalence studies in French Polynesia and Fiji found that levels of ZIKV neutralizing antibodies decrease with time [15]. If the fall in antibody levels means that people become susceptible to infection again, population level ZIKV immunity might be declining already.…”
Section: Introductionmentioning
confidence: 99%
“…The duration of protective immunity induced by ZIKV infection remains uncertain, since immunity to ZIKV infection was not studied extensively before the 2013 outbreaks. Evidence from seroprevalence studies in French Polynesia and Fiji found that levels of ZIKV neutralizing antibodies decrease with time [15]. If the fall in antibody levels means that people become susceptible to infection again, population level ZIKV immunity might be declining already.…”
Section: Introductionmentioning
confidence: 99%
“…According to Matheus et al . [21] and our study (data not shown), IgG raised against ZIKV and ZEDIII were still present, with at least 50% of the maximum ODr, after 300 DPSO and up to several years after infection [27]. This minor limitation could allow us to carry out retrospective seroprevalence studies of the ZIKV outbreak, whereas detecting ZIKV-induced IgG with ZEDIII could be used to detect recent past infections in populations at risk.…”
Section: Discussionmentioning
confidence: 78%
“…Nevertheless, the seroprevalence in our cohort did not significantly change during the 12-month study period. By contrast, Handerson et al found that the seroprevalence of ZIKV in French Polynesia and Fiji significantly declined over 18 months in adults but persisted in children [ 28 ]. Although we do not have sufficient information on the seroprevalence of Zika in Thailand prior to the 2016 outbreak, it is unclear whether the absence of changes in seroprevalence in this study were related to antibody persistence or a natural boost of immunity in this area.…”
Section: Discussionmentioning
confidence: 99%